PENERAPAN METODE PANTAU, PANGKAS, PADUKAN, PANGGIL (4P) UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA DALAM MERINGKAS CERITA - Widyastuti, Linda; Iswara, Prana Dwija; Isrok’atun, Isrok’atun (Jurnal Pena Ilmiah, 2017)
In skill writing students particular learning the indonesian language should owned by each student because that easier to understand every word learned it.In terms of summarizing, students is expected to develop a language she had own.One strategy that can be used teachers by using the method observation, prune, pair, call ( 4P ), can solve the problems in terms of summarizing story.Through this method students will be easy working on a summary clearly, short, and dense. Can then be packed into several a sentence or paragraph.Occurring at the time of in the field, not all the teacher use this method when learning summarizing ongoing.Because this method rarely worn in primary schools.This article discuss regarding the application of observation method, prune, padukan, call ( 4P) to improved the skills of writing students in summarizing story in grade 5 at SDN Pasanggrahan 2 kecamatan sumedang south sumedang district.